2019
DOI: 10.4103/abr.abr_34_18
|View full text |Cite
|
Sign up to set email alerts
|

Possible Role of Cyclic AMP Response Element Binding/Brain-Derived Neurotrophic Factor Signaling Pathway in Mediating the Pharmacological Effects of Duloxetine against Methamphetamine Use-Induced Cognitive Impairment and Withdrawal-Induced Anxiety and Depression in Rats

Abstract: Background:Duloxetine is used for treating depression and anxiety. The current study evaluated the effects of duloxetine against methamphetamine withdrawal-induced anxiety, depression, and motor disturbances and methamphetamine use-induced cognitive impairments.Materials and Methods:Ninety-six adult male rats were used for two independent experiments. Each experiment consisted of Groups 1 and 2 which received normal saline (0.2 ml/rat) and methamphetamine (10 mg/kg) respectively, Groups 3, 4, and 5 received bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 49 publications
(94 reference statements)
0
4
0
Order By: Relevance
“…Brain-derived neurotrophic factor is a direct target of CREB ( Barco et al, 2005 ), and cAMP-activated phosphorylated CREB regulates the expression of neurotrophic factors such as BDNF and NGF ( Ortega-Martinez, 2015 ). The cAMP/CREB/BDNF pathway has been shown to be an important mechanism of action in traditional Chinese medicine ( Cai et al, 2022 ) and novel antidepressants such as vortioxetine ( Ramezany et al, 2019 ). In the hippocampal mRNA sequencing of Sig-1R knockout mice, the cAMP signaling pathway was significantly enriched.…”
Section: Discussionmentioning
confidence: 99%
“…Brain-derived neurotrophic factor is a direct target of CREB ( Barco et al, 2005 ), and cAMP-activated phosphorylated CREB regulates the expression of neurotrophic factors such as BDNF and NGF ( Ortega-Martinez, 2015 ). The cAMP/CREB/BDNF pathway has been shown to be an important mechanism of action in traditional Chinese medicine ( Cai et al, 2022 ) and novel antidepressants such as vortioxetine ( Ramezany et al, 2019 ). In the hippocampal mRNA sequencing of Sig-1R knockout mice, the cAMP signaling pathway was significantly enriched.…”
Section: Discussionmentioning
confidence: 99%
“…In the chronic unpredictable stress animal model, CREB expression was inhibited in the hippocampal CA1 region; however, CREB levels recovered after antidepressant treatment [ 33 ]. Through modulation of cAMP-CREB-BDNF and other similar signaling pathways, numerous neuroprotective agents have been developed against neurodegenerative and neurobehavioral disorders [ 34 ]. This study observed that the PKA, p -CREB, and p -Trkb (BDNF-specific receptor) expressions were significantly increased after the GLP-1 treatment to the culture medium of HT22 cells, which were damaged by CORT + HG, suggesting that GLP-1 could up-regulate the cAMP-CREB-BDNF signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Fluoxetine increased the hypothalamic BDNF expression in mice [ 52 ], while milnacipran enhanced BDNF protein and mRNA levels in the mouse cerebral cortex [ 53 ]. On the other hand, duloxetine activated the BDNF protein expression in brains of rats subjected to the methamphetamine model of anxiety [ 54 ]. Desipramine, fluoxetine, and tianeptine increased the BDNF mRNA and protein expression in stressed rats [ 55 ].…”
Section: Discussionmentioning
confidence: 99%